An Analysis of Crisis Decision-Making: The Spanish-American War Case, 1898 - Vanderelst, Wilfried (My University, 1969)
This paper has two related goals: (1) to examine the impact of crisis, in general, and stress, in particular, on certain aspects of foreign policy-making; and, (2) to understand the motivations underlying the actions of American decision-makers within the political environment of 1898. The data is derived through a content analysis of documents written by certain "key" American decision- makers during the sixteen weeks prior to the outbreak of the Spanish American war in 1898.
Keywords: Political Science; Political Science